Camel Clinical Biochemistry and Hematology - Faye, Bernard (Springer International Publishing, 2018)
This work brings together a wealth of data regarding the reference values and factors of variation in biochemical parameters used by camel veterinarians and scientists to determine these animals' nutritional and clinical status. It also explores several technical aspects involved in determining these parameters, sampling procedures, and essential elements in the interpretation of the results. Though many texts are available on small and large ruminants, much less is known about species confined to the marginal zones of tropical and Mediterranean countries, such as camels. This book addresses precisely this research gap, on the one hand by presenting an extensive review of the literature, and on the other by synthesizing the outcomes of the authors' numerous previous works. In veterinary medicine, blood tests to help diagnose diseases in cattle were first proposed nearly a century ago, but were mainly developed in the 1960s, initially at specialized research or veterinary services laboratories, and eventually, with the advent of new equipment and the miniaturization of the analyzers, finding their way into veterinarians' cabinets. Beyond their diagnostic value, veterinary surgeons and zootechnicians also speculated on the potential use of blood tests to evaluate animals' nutritional status. Thus, a whole range of analyses are now proposed to the stakeholders responsible for animal health. Such analyses could help to define a metabolic profile, which would offer a valuable decision-making tool for experts and researchers alike.